Chapter 8
Taylor and Laurent Series
We think in generalities, but we live in details.
A. N. Whitehead
8.1
Power Series and Holomorphic Functions
We will see in this section that power series and holomorphic functions are intimately related. In
fact, the two cornerstone theorems of this section are that any power series represents a holomorphic
function, and conversely, any holomorphic function can be represented by a power series.
We begin by showing a power series represents a holomorphic function, and consider some of
the consequences of this:
Theorem 8.1.
Suppose
f
(
z
) =
k
≥
0
c
k
(
z
−
z
0
)
k
has radius of convergence
R
. Then
f
is holo
morphic in
{
z
∈
C
:

z
−
z
0

< R
}
.
Proof.
Given any closed curve
γ
⊂
{
z
∈
C
:

z
−
z
0

< R
}
, we have by Corollary 7.27
γ
k
≥
0
c
k
(
z
−
z
0
)
k
dz
= 0
.
On the other hand, Corollary 7.26 says that
f
is continuous. Now apply Morera’s theorem (Corol
lary 5.17).
A special case of the last result concerns power series with infinite radius of convergence: those
represent entire functions.
Now that we know that power series are holomorphic (i.e., di
ff
erentiable) on their regions of
convergence we can ask how to find their derivatives.
The next result says that we can simply
di
ff
erentiate the series “term by term.”
Theorem 8.2.
Suppose
f
(
z
) =
k
≥
0
c
k
(
z
−
z
0
)
k
has radius of convergence
R
. Then
f
(
z
) =
k
≥
1
k c
k
(
z
−
z
0
)
k
−
1
,
and the radius of convergence of this power series is also
R
.
82
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
CHAPTER 8.
TAYLOR AND LAURENT SERIES
83
Proof.
Let
f
(
z
) =
k
≥
0
c
k
(
z
−
z
0
)
k
. Since we know that
f
is holomorphic in its region of conver
gence we can use Theorem 5.1. Let
γ
be any simple closed curve in
{
z
∈
C
:

z
−
z
0

< R
}
. Note
that the power series of
f
converges uniformly on
γ
, so that we are free to interchange integral and
infinite sum. And then we use Theorem 5.1
again
, but applied to the function (
z
−
z
0
)
k
. Here are
the details:
f
(
z
) =
1
2
π
i
γ
f
(
w
)
(
w
−
z
)
2
dw
=
1
2
π
i
γ
k
≥
0
c
k
(
w
−
z
0
)
k
(
w
−
z
)
2
dw
=
k
≥
0
c
k
·
1
2
π
i
γ
(
w
−
z
0
)
k
(
w
−
z
)
2
dw
=
k
≥
0
c
k
·
d
dw
(
w
−
z
0
)
k
w
=
z
=
k
≥
0
k c
k
(
z
−
z
0
)
k
−
1
.
The last statement of the theorem is easy to show: the radius of convergence
R
of
f
(
z
) is at least
R
(since we have shown that the series converges whenever

z
−
z
0

< R
), and it cannot be larger
than
R
by comparison to the series for
f
(
z
), since the coe
ﬃ
cients for (
z
−
z
0
)
f
(
z
) are bigger than
the corresponding ones for
f
(
z
).
Naturally, the last theorem can be repeatedly applied to
f
, then to
f
, and so on. The various
derivatives of a power series can also be seen as ingredients of the series itself. This is the statement
of the following
Taylor
1
series expansion
.
Corollary 8.3.
Suppose
f
(
z
) =
k
≥
0
c
k
(
z
−
z
0
)
k
has a positive radius of convergence. Then
c
k
=
f
(
k
)
(
z
0
)
k
!
.
Proof.
For starters,
f
(
z
0
) =
c
0
. Theorem 8.2 gives
f
(
z
0
) =
c
1
. Applying the same theorem to
f
gives
f
(
z
) =
k
≥
2
k
(
k
−
1)
c
k
(
z
−
z
0
)
k
−
2
and
f
(
z
0
) = 2
c
2
. We can play the same game for
f
(
z
0
),
f
(
z
0
), etc.
This is the end of the preview.
Sign up
to
access the rest of the document.
 Fall '11
 Staff
 Power Series, Taylor Series, Mathematical Series

Click to edit the document details